2000
DOI: 10.1614/0890-037x(2000)014[0057:eaeowm]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Economics of Weed Management in Glyphosate-Resistant Corn (Zea mays)1

Abstract: Field experiments were conducted in 1997 and 1998 near Columbia and Novelty, MO, and Urbana, IL, to evaluate crop injury, weed control, corn yield, and net economic returns provided by weed control programs in glyphosate-resistant corn. The herbicide programs evaluated included acetochlor preemergence (PRE) followed by (fb) glyphosate with or without atrazine postemergence (POST) and total POST programs consisting of single and sequential applications of glyphosate alone and tank-mixed with actochlor, atrazine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
114
1
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(128 citation statements)
references
References 20 publications
11
114
1
2
Order By: Relevance
“…rudis in corn in Missouri required two applications of glyphosate or glufosinate in combination with residual herbicides (Hellwig et al 2003). Single applications were much less effective, unless combined with a residual herbicide, such as atrazine in corn, or sulfentrazone in soybeans Dirks et al 2000a;Johnson et al 2000;Beyers et al 2002;Nolte and Young 2002a, b). Control with single glyphosate applications in soybeans increased as row spacing decreased from 76 to 19 cm .…”
Section: Response To Herbicides and Other Chemicalsmentioning
confidence: 99%
“…rudis in corn in Missouri required two applications of glyphosate or glufosinate in combination with residual herbicides (Hellwig et al 2003). Single applications were much less effective, unless combined with a residual herbicide, such as atrazine in corn, or sulfentrazone in soybeans Dirks et al 2000a;Johnson et al 2000;Beyers et al 2002;Nolte and Young 2002a, b). Control with single glyphosate applications in soybeans increased as row spacing decreased from 76 to 19 cm .…”
Section: Response To Herbicides and Other Chemicalsmentioning
confidence: 99%
“…Twomlow et al (1997) reported that in maize the driest soil profiles and lowest yields were observed under the unweeded control. Johnson et al (2000) described that increasing corn population to the recommended level would be the first approach to increase corns competitive ability against weeds using narrow rows which appears to have less potential for improving weed control. Sinha et al (2000) reported that nutrient depletion by weeds was minimum under hand weeding while it was maximum 23.18 kg N, 4.92 kg P and 27.83 kg Kha -1 under weedy check in maize in calcareous soils of North Bihar.…”
Section: Critical Period Of Crop -Weed Competition In Maizementioning
confidence: 99%
“…Glyphosate-resistant maize is advantageous compared to conventional hybrids. According to Johnson et al (2000), two post emergence glyphosate applications on corn can provide better weed control than a single glyphosate application, especially if interfering weeds are controlled at heights less than 15 cm. Application of glyphosate at 0.84 kg ha -1 followed by 0.63 kg ha -1 as early post emergence provided effective control of shattercane (100 per cent) and giant foxtail (99 per cent) while single application of glyphosate provided only 58 per cent and 69 per cent of shattercane and giant foxtail, respectively at Columbia (Hans and Johnson, 2002).…”
Section: Weed Control Efficiency Of Glyphosate Tolerant Maizementioning
confidence: 99%
See 1 more Smart Citation
“…The development of herbicide-resistant crops allows weed control by nonselective postemergence (POST) herbicides, such as glyphosate and glufosinate, widening the array of weed management programs available to producers [5][6][7]. Both glyphosate and glufosinate control a wide range of weeds in herbicide-resistant crops [7] with little, if any, crop injury [8,9].…”
Section: Introductionmentioning
confidence: 99%